The Aga Khan, East Africa and Russia’s Image: Tracing the Lesser-Known Dimensions of the AKDN’s Work - Mayya V. Nikolskaya; Vasilii V. Vinogradov (Vestnik RUDN. International Relations)
The study examines the role of the Aga Khan Development Network (AKDN) in shaping Russia’s image in East Africa. The AKDN is viewed as an independent non-governmental organization (NGO) in East Africa, whose stance on Russia currently coincides with that of the collective West. The authors proceed from the assumption that since 2022, the AKDN, in particular its media branch, the Nation Media Group , has sought to portray Russia in a negative light. The study consists of two sections. The first section provides an overview of the AKDN’s activities in East Africa since the emergence of Ismaili communities in the region and describes the key areas of its work on a country-by-country basis, as delineated on the official website of the organization. The analysis pays special attention to humanitarian, educational, and media projects, which give the organization more advantage in terms of shaping images, values, and ideas. After analyzing the activities of the AKDN, the authors conclude that the organization has built substantial social capital in East Africa through such development projects. The second section aims to verify the initial hypothesis of the AKDN’s anti-Russian slant through building a corpus of news items from outlets affiliated with the AKDN, using methodology for text analysis such as named entity recognition, LDA machine learning, and sentiment analysis of publications throughout the year 2023. The resulting tonality, topics and geographical coverage of the news publications allow the authors to conclude that the media do indeed construct a negative image of Russia in East Africa by invoking connotations of aggression, conflict and destabilization in Africa and the entire world, which may be caused by the AKDN’s orientation towards the West as well as differences between the AKDN and Russia’s positions in Central Asia. It is recommended that Russia take into account the power and resources that the AKDN employs in the information field.